Využití databáze H2 v JBoss aplikačním serveru - Penčikov, Michal (Vysoké učení technické v Brně. Fakulta informačních technologií, 2010)
JBoss aplikační server (AS) je open source implementace standardu Java EE. Jeho aktuálně používaná databáze pro potřeby testování, HSQL, má některá podstatná omezení, proto existují požadavky na využití jiných databází, použitelných při testování JBoss AS. H2 je relativně nová relační databáze, napsaná čistě v Javě. Tato práce popisuje, jak lze JBoss AS nakonfigurovat, aby místo HSQL databáze používal H2 databázi. Dále uvádí výsledky testů, provedených po této rekonfiguraci a identifikuje problémy, které bude nutno vyřešit, aby JBoss AS mohl používat databázi H2.

The JBoss application server (AS) is an open source implementation of the Java EE standard. Currently, the JBoss AS uses the HSQL database system for testing purposes. This database system has certain limitations. Therefore, there is a need to use another database system for testing of JBoss AS. H2 is a relatively new relational database entirely written in Java. This thesis describes configuring JBoss AS so it is able to use the H2 database instead of HSQL database. The thesis then provides JBoss AS test results obtained by running tests after reconfiguration and identifies issues that need to be solved before deployment of H2 database.
Use H2 Database in JBoss Application Server
Keywords: Java EE; Java; JBoss; databáze; H2; aplikační server; Hypersonic; HSQL; Java EE; Java; JBoss; database; H2; application server; Hypersonic; HSQL